Prevalence of depression among medical students in Africa: Systematic review and meta-analysis. - Chilot Kassa Mekonnen; Hailemichael Kindie Abate; Zerko Wako Beko; Alebachew Ferede Zegeye; Abere Woretaw Azagew (PLoS ONE)
Introduction Depression has become a major health problem that students in a University encounter during their study life. At least one-third and possibly up to one-half of medical students show some form of psychological distress during their medical school. Aggregated evidence is scarce in Africa though there are published articles with various outputs. Therefore, this systematic review and meta-analysis aimed to pool those outputs to draw concert information crucial for devising strategies to tackle depression among students at the University. Objective To determine the pooled prevalence of depression among African medical students. Method Original articles about the prevalence of depression among African medical students were searched through known and international databases (PubMed, Scopus, Web of Science, and Cochran Library) and search engines (Google and Google Scholar). Data were extracted using a standard data extraction checklist that was developed according to Joanna Briggs Institute (JBI). The I2 statistics were used to identify heterogeneity across studies. Funnel plot asymmetry and Egger's tests were used to check for publication bias. A Random effect model was used to estimate the pooled prevalence of depression among medical students in Africa. Statistical analysis was conducted using STATA version 11 software. Result A total of 31 cross-sectional observational studies which provided information about the prevalence of depression among medical students were included in this systematic review and meta-analysis. The overall pooled prevalence of depression among medical students in Africa was 38.80% [95%CI (29.55, 48.05). Being a female medical student was [AOR = 0.25, 95%CI (0.15, 0.42)] and being a second-year medical student was [AOR = 0.26, 95%CI (0.10, 0.68)] times less likely to have depression. Conclusion Depression affects well over one-third of medical students in Africa. Moreover, this systematic review and meta-analysis revealed that female medical students were less likely to develop depression. Therefore, this result suggested that medical schools or Universities and concerned authorities better offer possible early detection and prevention programs as per the magnitude. Furthermore, there has to be further research to figure out the potential factors perhaps using both qualitative and quantitative research approaches.